2004
DOI: 10.1103/physrevb.70.157102
|View full text |Cite
|
Sign up to set email alerts
|

Reply to “Comment on ‘Conduction states in oxide perovskites: Three manifestations ofTi3+Jahn-Teller polarons in barium titanate’”

Abstract: A concise overview on the available theoretical and experimental data concerning the structure of oxygen vacancies in the oxide perovskites is given. In this context the statements made in the Comment are discussed.There is no doubt that neutral oxygen leaves an oxygen perovskite, OP, ͑ABO 3 ͒ crystal when annealed in a reducing atmosphere. For each oxygen atom lost two electrons remain in the crystal.What is the structure of the resulting defects? We start by characterizing the present knowledge concerning is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Each V O in undoped BaTiO 3 donates up to two electrons, which are generally localized on Ti, so that a completely ionized V O induces the Ti 3+ state in two Ti 4+ ions. 53,54 The external electronic shell of Ti +3 is 3d 1 , or an electron is doped in the empty 3d shell. The five degenerate d orbitals are already split into three T 2g (d xy , d yz and d xz ) and two E g (d 3z 2 −r 2 and d x 2 −y 2 ) orbitals by the octahedral environment of Ti, which can be further split by octahedral distortions, giving rise to the Jahn-Teller (JT) effect.…”
Section: Cooperative Jahn-teller Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each V O in undoped BaTiO 3 donates up to two electrons, which are generally localized on Ti, so that a completely ionized V O induces the Ti 3+ state in two Ti 4+ ions. 53,54 The external electronic shell of Ti +3 is 3d 1 , or an electron is doped in the empty 3d shell. The five degenerate d orbitals are already split into three T 2g (d xy , d yz and d xz ) and two E g (d 3z 2 −r 2 and d x 2 −y 2 ) orbitals by the octahedral environment of Ti, which can be further split by octahedral distortions, giving rise to the Jahn-Teller (JT) effect.…”
Section: Cooperative Jahn-teller Transitionmentioning
confidence: 99%
“…The five degenerate d orbitals are already split into three T 2g (d xy , d yz and d xz ) and two E g (d 3z 2 −r 2 and d x 2 −y 2 ) orbitals by the octahedral environment of Ti, which can be further split by octahedral distortions, giving rise to the Jahn-Teller (JT) effect. 55 The Ti 3+ ions are usually observed in acceptor doped titanates, 53,54 where, at low concentrations, they form polarons or bipolarons, without particular effects on the structure. It is also suggested that the JT distortions of Ti 3+ in BaTiO 3 may stabilize the hexagonal phase (h-BT) over the cubic one under strongly reducing conditions, but this occurs at the very high sintering temperatures ∼ 1400 • C, which can be slightly lowered by doping strongly JT active ions in the Ti site.…”
Section: Cooperative Jahn-teller Transitionmentioning
confidence: 99%
“…7,[20][21][22][23] For perovskite oxides such as SrTiO 3 , the electronic structure of the F-type defects is a subject of a long debate. 24 Several theoretical studies have suggested major and identical contributions from the 3d orbitals of the two Ti ions on both sides of O vacancy to the electron density of the F center, 13,19,26 although others indicate a partial or total localization of the electrons in the vacancy. 27 The position of the F center level in the optical band gap is also somewhat controversial 19,25 although indirect experimental data based on conductivity measurements suggest that the neutral F center is a quite shallow defect.…”
Section: Introductionmentioning
confidence: 99%
“…However, convincing evidence is lacking that the isolated native vacancy defects have accessible EPR active states in perovskite oxides [9]. Direct imaging of O vacancies has been demonstrated using aberration corrected transmission electron microscopy (TEM) [10], or annular-dark-field TEM, supported by electron energy-loss spectroscopy (EELS) [11].…”
mentioning
confidence: 99%